Conceptualizing a Resilience Framework for Digital-First Organizational Structures - Elahi, Taraneh; Karimzadeh, Iman; Mousavi, Mohammad Reza (Future of Work and Digital Management Journal, 2024)
This study aims to conceptualize a multidimensional resilience framework specifically tailored to digital-first organizational structures by exploring how resilience is experienced, enacted, and sustained in technologically integrated environments. This qualitative research employed a phenomenological design to investigate resilience mechanisms in digital-first organizations. Data were collected through semi-structured interviews with 28 participants from various industries in Tehran, including IT leads, HR professionals, project managers, and executives. Participants were purposefully selected based on their active involvement in digitally embedded operations. Interviews continued until theoretical saturation was achieved. All interviews were transcribed and thematically analyzed using NVivo software. Open, axial, and selective coding procedures were used to identify recurring patterns, subthemes, and overarching categories of resilience. Analysis revealed three major themes: structural adaptability, human and cultural resilience, and strategic foresight and learning orientation. Within these categories, key subthemes included decentralized decision-making, agile workflows, emotional support systems, shared purpose, feedback loops, and innovation culture. Findings showed that resilient digital-first organizations exhibit high degrees of operational flexibility, technology-enabled learning systems, and psychologically safe work climates. Cross-functional integration and modular digital infrastructure significantly enhanced the capacity to anticipate, absorb, and adapt to disruptions. The role of leadership emerged as a central facilitator, mediating both technological transitions and cultural cohesion. Results suggest that resilience in digital-first contexts is not merely reactive but deeply proactive and systemic. Resilience in digital-first organizations is shaped by an intricate interaction of structural design, cultural practices, and strategic adaptability. Unlike conventional resilience models, digital-first resilience requires reimagining leadership, workflows, and learning systems as dynamic and interdependent components. This study contributes a context-specific framework that supports organizations in developing comprehensive, future-ready resilience strategies.